Kristevan Femininity and Negative Theology in Christopher Marlowe’s Tamburlaine, I and II - Takapoui, Tina (Early Modern Culture Online, 2018)
Christopher Marlowe’s characters, brought along from far-off corners of history to the centre stage, are rid of the illusive integrity of Selfhood. His plays are also famous for their reluctance to favour domestic and female atmosphere. Despite such views, Marlowe’s drama enjoys a specific aura of femininity which is pressed by contemporary French feminist theoreticians, namely Julia Kristeva who finds the term essentially irrelevant to genders, but a spatial and temporal concept. In the present study, such supposition of the absence of femininity in Marlovian drama is questioned, doubted, and eventually rejected. The outlandish characters are also found in the heart of the very society Marlowe was living, only in a theatrical disguise, drawn back into spotlight from the level of the social unconscious.